Hemodynamic and symptomatic improvement after delayed thrombolysis with Reteplase in a patient with massive bilateral pulmonary emboli. Issue 1 (January 2015) - Sharif-Kashani, Babak; Kiani, Arda; Bakhshayesh-Karam, Mehrdad; Sheybani-Afshar, Faezeh; Behzadnia, Neda; Naghash-Zadeh, Farah
<x xml:space="preserve">Abstract</x> Most patients surviving the acute phase of pulmonary embolism will recover with no residue. But, 2–4% of patients will progress to chronic thromboembolic pulmonary hypertension. In this group, usually a 'Honey moon' period is seen but a few may show progression with ongoing symptoms despite medical treatment. In this case report, we review a patient in whom delayed thrombolytic therapy was administered due to progressive symptoms after 21 days. Her condition was stabilized. The early posttreatment computed tomographic pulmonary angiography (CTPA) showed incomplete resolution, but after 6 months she was functional class I with a normal CTPA and echocardiography.